2020
DOI: 10.1161/jaha.119.014836
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and 90‐Day Mortality After Hospitalization for Heart Failure in the REGARDS Study

Abstract: Background Outcomes following heart failure ( HF ) hospitalizations are poor, with 90‐day mortality rates of 15% to 20%. Although prior studies found associations between individual social determinants of health ( SDOH ) and post‐discharge mortality, less is known about how an individuals’ total burden of SDOH affects 90‐day mortality. Methods and Results We included participants of the REG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 50 publications
2
60
1
1
Order By: Relevance
“…Due to this complex interaction, efforts to quantify the impact of any single factor on a health outcome are likely inadequate, as they fail to capture the entire effect of an individual's social context. Our findings suggest that the clustering of SDOH may indicate a more substantial need to address these risk factors given the strong and wide influence SDOH have on a broad range of health conditions, clinical outcomes (e.g., cardiovascular disease, stroke, diabetes) 3,9,11,18,19 , and risk prediction models used by payors. 3,4,20 We note that while these data indicate a small effect size, when applied to a national lens, even small, incremental increases in hospitalization risk could have substantial impact.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Due to this complex interaction, efforts to quantify the impact of any single factor on a health outcome are likely inadequate, as they fail to capture the entire effect of an individual's social context. Our findings suggest that the clustering of SDOH may indicate a more substantial need to address these risk factors given the strong and wide influence SDOH have on a broad range of health conditions, clinical outcomes (e.g., cardiovascular disease, stroke, diabetes) 3,9,11,18,19 , and risk prediction models used by payors. 3,4,20 We note that while these data indicate a small effect size, when applied to a national lens, even small, incremental increases in hospitalization risk could have substantial impact.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Johnston et al recently explored the association of several social risk factors with preventable hospitalizations but did not examine the combinatorial impact of these SDOH on hospitalization. Although previous assessments have examined the incremental impact of SDOH on a variety of other clinical outcomes (e.g., diabetes, stroke risk, heart failure mortality), [9][10][11][12] to our knowledge no previous work has explored the cumulative impact of multiple SDOH on hospitalizations. Given the interconnectedness of these risk factors, assessing the impact of these vulnerabilities in aggregate, rather than individually, would be a more representative assessment of their influence on hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Against this multifaceted backdrop, people with HF who are of non-white race or otherwise marginalized, those with modest educational attainment, economic instability, poor living conditions, or lacking in social support or access to effective health care structures, face worse outcomes with this condition. This vulnerability was evident in a study of 690 Medicare beneficiaries > 65 years discharged alive after HF hospitalization who showed a close to threefold increase in 90-day mortality if they were exposed to only one of nine possible SDOH as defined in the REGARDS (Reasons for Geographic and Racial Differences in Stroke) study, even when patients discharged to hospice were excluded [ 93 ]. The AHA statement explicitly highlighted poor access to PC in such disadvantaged populations, and a systematic review has demonstrated that people living in high-income countries with low socioeconomic standing experience poorer quality end-of-life care with increased use of acute medical services in the 3-month period before death, higher rates of death in hospital, and lesser involvement of specialist PC services during their last year of life [ 94 ].…”
Section: Social Carementioning
confidence: 99%
“…A simple count of SDVs may be a quick and easy indicator of patients who are at increased risk of heart failure. REGARDS, a United States national, bi-racial, prospective cohort study of 30 239 community-dwelling adults who have been followed for 10+ years, 2 is well-suited for studying the influence of SDVs on a variety of cardiovascular-related end points including heart failure, 1 stroke, 3 90-day mortality after a heart failure hospitalization, 4 and coronary heart disease. 5 …”
Section: In Responsementioning
confidence: 99%